Lumican and versican protein expression are associated with colorectal adenoma-to-carcinoma progression. - Meike de Wit; Beatriz Carvalho; Pien M Delis-van Diemen; Carolien van Alphen; Jeroen A M Beliën; Gerrit A Meijer; Remond J A Fijneman (PLoS ONE, 2017)
One prominent event associated with colorectal adenoma-to-carcinoma progression is genomic instability. Approximately 85% of colorectal cancer cases exhibit chromosomal instability characterized by accumulation of chromosome copy number aberrations (CNAs). Adenomas with gain of chromosome 8q, 13q, and/or 20q are at high risk of progression to cancer. Tumor progression is also associated with expansion of the extracellular matrix (ECM) and the activation of non-malignant cells within the tumor stroma. The glycoproteins versican and lumican are overexpressed at the mRNA level in colon carcinomas compared to adenomas, and are associated with the formation of tumor stroma.The aim of this study was to characterize versican and lumican protein expression in tumor progression and investigate their association with CNAs commonly associated with adenoma-to-carcinoma progression.Tissue microarrays were constructed with colon adenomas and carcinomas that were characterized for MSI-status and DNA copy number gains of chromosomes 8q, 13q and 20q. Sections were immunohistochemically stained for lumican and versican. Protein expression levels were evaluated using digitized slides, and scores were finally dichotomized into a positive or negative score per sample.Lumican and versican expression were both observed in neoplastic cells and in the tumor stroma of colon adenomas and carcinomas. Lumican expression was more frequently present in epithelial cells of carcinomas than adenomas (49% versus 18%; P = 0.0001) and in high-risk adenomas and carcinomas combined compared to low-risk adenomas (43% versus 16%; P = 0.005). Versican staining in the tumor stroma was more often present in high-risk adenomas combined with carcinomas compared to low-risk adenomas (57% versus 36%; P = 0.03) and was associated with the presence of gain of 13q (71% versus 44%; P = 0.04).Epithelial lumican and stromal versican protein expression are increased during colorectal adenoma-to-carcinoma progression.